Critical Analysis of Selected Issues of Sufism in the Light of Tafsīr Rūḥ al Ma’ānī - Zaman, Wali; Uddin, Muhammad Fakhar; Khan, Irfan Ullah (Journal of Islamic and Religious Studies, 2021)
Mahmood bin ‘Abdullah Al Ālūsī, author of Tafsīr Rūḥ al Ma’ānī, is a well-known scholar of Islamic world. In this book, besides describing the basics of Islamic education, he also discussed the ideas of Ṣūfiyā’ and criticized them in the light of Sharī’ah. After describing the ideas of Ṣūfiyā’ along with the logic behind, he critically analyzes their views and presents his own point of view about the issue as a concluding note. This paper the Prophethood in Animals, affirmation of the rationality, consciousness and soul in inanimate objects, disagreement in the feeling of being in pain and owe feelings in inanimate objects, the legitimacy of dance and songs are presented. The paper concludes that Al Ālūsī completely rejects the Ṣūfī opinion in all the issues except about the prophethood in animals as he does not oppose their opinion, nor he imposes fatwa of disbelief on them.